Stability Analysis of Mathematical Modeling of Interaction between Target Cells and COVID-19 Infected Cells - Sugiyanto Sugiyanto; Mansoor Abdul Hamid; Alya Adianta; Hanny Puspha Jayanti; Muhammad Ja'far Luthfi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2021)
The stability analysis in this mathematical model was related to the infection of the Coronavirus Disease 2019 (Covid-19). In this mathematical model there were two balance points, namely the point of balance free from Covid-19 and the one infected with Covid-19. The stability of the equilibrium point was influenced by all parameters, i.e. target cells die during each cycle, number of target cells at = 0, target cells infected during each cycle based on virion unit density, effective surface area of the network, the ratio of the number of virus particles to the number of virions, infected cells die during each cycle, the number of virus particles produced by each infected cell during each cycle, and virus particles die during each cycle. In the simulation model, immunity is divided into high, medium and low immunity. For high, moderate and low immunity, respectively, the highest number of target cells is in high, medium and low immunity, whereas for the number of infected cells and the number of Covid-19, it is in the opposite sequence of the number of target cells.